Index of Library Users Satisfaction At Governance Institute of Home Affairs (IPDN) Nusa Tenggara Barat Campus in 2021 - Muaidi, Muh.; Wijanaraga, I Wayan; Mulyadi, Muhamad; Wijaya, I Dewa Made Putra; Arab, Agussalim Mad (Indonesian Journal of Librarianship, 2021)
Background: Library user satisfaction is one of the benchmarks in public service implementation. However, a measurement which is based on the indicators stated in the Ministry Regulation of State Apparatus Empowerment and Bureaucratic Reform (PANRB) Number 14 of 2017 on Guidelines of Public Satisfaction Survey Creation in Public Service Administrator Unit, has never been carried out in the Library of Governance Institute of Home Affairs NTB Campus. A similar survey was conducted in 2018 but used different indicators. Thus, a study on library users’ satisfaction index of the library services of Governance Institute of Home Affairs NTB Campus was conducted by the researchers. Purpose: This research aims at determining the index of library users’ satisfaction towards the library service of Governance Institute of Home Affairs Nusa Tenggara Barat Campus. Method: This study uses a quantitative descriptive approach along with a survey method which refers to the measurement of library users’ satisfaction index and is supported by secondary data with literature reviews from the result of previous relevant studies. Result: Index of service satisfaction on the system, mechanism, and procedure feature is 3,252 (scale of 3) and belongs to the good category. Requirements feature is 3,149 (scale of 3) and belongs to the good category. A feature based on completion time is 3,119 (scale of 3) and belongs to the good category. A feature according to costs/tariffs is 3,305 (scale of 3) and belongs to the good category. A feature on product specifications for the type of services is 3,809 (scale of 3) and belongs to the good category. A feature on executing officer’s ability is 3,179 (scale of 3) and belongs to the good category. A feature on executing officer’s behavior is 3,311 (scale of 3) and belongs to the good category. A feature based on handlings of complaints, suggestions, and feedbacks is 3,109 (scale of 3) and belongs to the good category, while a feature on infrastructure is 3,502 (scale of 3) and belongs to the good category. On the other hand, the service satisfaction level in 2018 is higher than the service satisfaction level in 2021. If the amount of average of these levels is acquired, it can be concluded that there is a 7% decline of every service performance feature. Conclusion: The study suggests that even though there is a decline from Muaidi’s research findings in 2018, the Index of Library Users Satisfaction towards the library service of Governance Institute of Home Affairs NTB Campus in 2021 can be considered as “good” with the value of Public Satisfaction Index (IKM) 3,194. Keywords: Library; Library Users; Public Satisfaction Index; Library of Governance Institute of Home Affairs NTB Campus.